Consumption of benthic cyanobacterial mats on a Caribbean coral reef - Ethan C. Cissell (Nature Portfolio, 2019)
Abstract Herbivory is an important process in the general structuring of coral reef benthic communities. However, evidence of its ability to control coral reef benthic cyanobacterial mats, which have recently proliferated on reefs worldwide, remains ambivalent. Here, we report that the French Angelfish (Pomacanthus paru), Striped Parrotfish (Scarus iseri), Rock Beauty (Holacanthus tricolor), Ocean Surgeonfish (Acanthurus bahianus), Blue Parrotfish (Scarus coeruleus), and Atlantic Blue Tang (Acanthurus coeruleus) consume benthic cyanobacterial mats on coral reefs in Bonaire, Netherlands. We documented the foraging patterns of P. paru and S. iseri, and found that benthic cyanobacterial mats comprised 36.7% ± 5.8% and 15.0% ± 1.53% (mean ± standard error) of the total bites taken by P. paru and S. iseri respectively. This magnitude of consumption suggests that grazing by reef fishes may represent a potentially important, but previously undocumented, top-down control on benthic cyanobacterial mats on Caribbean reefs.